2018
DOI: 10.1113/ep087278
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ATP synthase β‐subunit production rate and ATP synthase specific activity are reduced in skeletal muscle of humans with obesity

Abstract: The content of the beta subunit of the ATP synthase (β-F1-ATPase), which forms the catalytic site of the enzyme ATP synthase, is reduced in muscle of obese humans, along with reduced capacity for ATP synthesis. We studied 18 young (37 ± 8 years old) subjects of which nine were lean (BMI = 23 ± 2 kg/m2) and nine were obese (BMI = 34 ± 3 kg/m2) to determine the fractional synthesis rate (FSR) and gene expression of β-F1-ATPase, as well as the specific activity of the ATP synthase. FSR of β-F1-ATPase was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…The mitochondrial biogenesis and translation machinery is heavily dependent on cues from the nucleus [65] and physical activity [66] . Previous studies have demonstrated that obesity is associated with downregulation of mitochondrial transcripts [67] , lower ATP synthesis and decreased insulin sensitivity [68] . Alternatively, upregulation of mitochondrial pathways would lead to higher mitochondrial respiration and thereby increased reactive oxygen species (ROS) production [69] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial biogenesis and translation machinery is heavily dependent on cues from the nucleus [65] and physical activity [66] . Previous studies have demonstrated that obesity is associated with downregulation of mitochondrial transcripts [67] , lower ATP synthesis and decreased insulin sensitivity [68] . Alternatively, upregulation of mitochondrial pathways would lead to higher mitochondrial respiration and thereby increased reactive oxygen species (ROS) production [69] .…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in agreement with previous studies on PCOS that have documented that most of the genes associated with PCOS were found to be downregulated in the disease state [61] , [62] . Expectedly, many of these downregulated genes are enriched in relevant pathways for PCOS such as apoptosis [63] , angiogenesis [64] , oxidative-stress [65] , glucose metabolism [66] , steroid metabolism [67] , immune response [68] and circadian rhythm [69] . Ovarian and endometrial tissues share several commonly dysregulated genes …”
Section: Discussionmentioning
confidence: 99%
“…Until now, malfunction of F-ATP synthase has been associated with a variety of pathological conditions, such as cardiovascular [87] and neurodegenerative diseases [88], obesity and type 2 diabetes [89, 90], and cancer [91]. Despite such important evidence, F-ATP synthase has only recently been used as an effective drug target for disease conditions and for the regulation of energy metabolism [92], despite the fact that more than 300 natural and synthetic molecules are known to bind and inhibit this complex [93].…”
Section: F-atp Synthase As a Target For Drug Developmentmentioning
confidence: 99%
“…For example, several experimental studies have shown that DDT applied to isolated mitochondrion (the power plants of the cell) can inhibit ATPase activity and resulting ATP synthesis (the production of charged batteries). 39 As one would expect from such impaired mitochondrial metabolism, 40 adult mice whose mothers were treated with DDT had decreased energy expenditure and increased adipose mass despite no change in physical activity. 14 Although unmeasured increased calorie consumption among CHDS daughters with elevated maternal DDT levels could also explain their elevated risk of obesity, we know of no experimental evidence that maternal DDT exposure has perturbed this canonical obesity risk factor.…”
Section: Discussionmentioning
confidence: 99%